SAMA peptide, a rationally designed antimicrobial peptide - Mohammad Alsaggar, Alaa Al-Tarawneh, Yara Al Tall, Mohammad Al-Hazabreh (Journal of Applied Pharmaceutical Science, 2021)
Antimicrobial peptides (AMP) are gaining increasing attention as a potential alternative to existing antibiotics to tackle bacterial resistance. Herein, we aimed to design and examine a novel antimicrobial peptide with superior antimicrobial activity and safety profiles. The design relied on a hybridization approach of selected parts of two naturally existing peptides; the brevinin-1E and bombolitin IV peptides were used to design a novel peptide named SAMA, which was characterized in silico prior to experimental approaches. The antimicrobial and antibiofilm activities of SAMA were examined in vitro on representative control and multi-drug-resistant bacterial strains, alone or combined with five traditional antibiotics. The SAMA peptide displays strong and broad-spectrum antimicrobial effects against selected strains at concentrations of 5 to 15 µM. Moreover, 30–40 µM of the peptide was sufficient to eradicate the biofilmforming Gram-positive strains. Combining the SAMA peptide with traditional antibiotics displayed a synergistic or additive mode of action, which significantly reduced their needed MIC values. In addition, SAMA displayed potential anticancer properties against the adenocarcinoma cell line. Importantly, therapeutic concentrations of SAMA displayed minimal hemolytic activity. Therefore, this study demonstrated that AMP indeed offer favorable substitutes to current antibiotics for the management of infectious diseases. The SAMA peptide is a broad-spectrum AMP and a promising candidate for antimicrobial and anticancer drug development.
Keywords: Antimicrobial peptides, antibiotic resistance, antibiofilm activity, antimicrobial synergism, antimicrobial drug development